2015
DOI: 10.1590/2446-4740.0739
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the influence of stimuli color on Steady-State Visual Evoked Potentials

Abstract: Introduction:The main idea of a traditional Steady State Visually Evoked Potentials (SSVEP)-BCI is the activation of commands through gaze control. For this purpose, the retina of the eye is excited by a stimulus at a certain frequency. Several studies have shown effects related to different kind of stimuli, frequencies, window lengths, techniques of feature extraction and even classification. So far, none of the previous studies has performed a comparison of performance of stimuli colors through LED technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 27 publications
0
23
0
4
Order By: Relevance
“…Os autores de [15] afirmam que diferentes cores estão associadas a diferentes emoções e estados mentais; e a cor vermelha provocaria também maior ativação do estado mental. Entretanto, segundo o experimento realizado por [8], a cor vermelha é relatada como a menos confortável para os usuários.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Os autores de [15] afirmam que diferentes cores estão associadas a diferentes emoções e estados mentais; e a cor vermelha provocaria também maior ativação do estado mental. Entretanto, segundo o experimento realizado por [8], a cor vermelha é relatada como a menos confortável para os usuários.…”
Section: Resultsunclassified
“…Alguns estudos recentes [6,7,8,9, 10] avaliaram diferentes estímulos visuais com o objetivo de desenvolver ICMs confiáveis e confortáveis. No entanto, diversos aspectos ainda necessitam ser aprofundados para que tal técnica possa ser efetivamente utilizada no futuro.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Atau dapat dikatakan bahwa respon sinyal EEG terhadap beberapa kondisi yang ditentukan memiliki perbedaan yang tidak terlalu signifikan. Beberapa penelitian terkini telah dilakukan untuk mengamati pengaruh stimulus warna yang diberikan kepada seseorang terhadap sinyal EEG [8][9][10]. Perbedaan yang muncul dari beberapa stimulus warna memberikan hasil sinyal EEG yang cukup berbeda.…”
Section: Pendahuluanunclassified
“…Different stimuli have been used for SSVEP BCI-based applications, as reviewed by [14]. The same review also revealed that stimulation frequencies in the low (1-12 Hz) and medium (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) frequency band have been more often applied than those in the high frequency band (30-60 Hz). The first is graphic alternation, in which a simple form (circle, rectangles) is successively displayed and hidden at the preferred frequency.…”
Section: Related Workmentioning
confidence: 99%